2020
DOI: 10.3847/1538-4357/ab80ba
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Distribution of the Extremely Overionized Plasma Associated with the Supernova Remnant G359.1-0.5

Abstract: We report on the results of our detailed analyses on the peculiar recombining plasma of the supernova remnant (SNR) G359.1−0.5, and the interacting CO clouds. Combining Chandra and Suzaku data, we estimated the ionization state of the plasma with a careful treatment of the background spectrum. The average spectrum showed a remarkably large deviation of the electron temperature (∼0.17 keV) from the initial temperature (> 16 keV), indicating that the plasma is in a highly recombinationdominant state. On the othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…As mentioned above, the reported distances to G359.1-0.5 and G347.3-0.5 are controversial in the literature. For G359.1-0.5, our derived distance 3.29 ± 0.47 kpc confirmed that this SNR is in the foreground of the Galactic center at a distance of ∼4 kpc by Suzuki et al (2020). For G347.3-0.5, our extinction distance of 4.56 ± 0.58 kpc is consistent with the suggested distance of 6 ± 1 kpc by Slane et al (1999).…”
Section: Comparison With the Other Distancessupporting
confidence: 87%
See 3 more Smart Citations
“…As mentioned above, the reported distances to G359.1-0.5 and G347.3-0.5 are controversial in the literature. For G359.1-0.5, our derived distance 3.29 ± 0.47 kpc confirmed that this SNR is in the foreground of the Galactic center at a distance of ∼4 kpc by Suzuki et al (2020). For G347.3-0.5, our extinction distance of 4.56 ± 0.58 kpc is consistent with the suggested distance of 6 ± 1 kpc by Slane et al (1999).…”
Section: Comparison With the Other Distancessupporting
confidence: 87%
“…Moreover, the distances to some SNRs are still controversial, such as SNR G359.1-0.5. As summarized in Suzuki et al (2020) and Eppens et al (2020), there are suggestions that the SNR located at the Galactic Center, 8.5 kpc, or the foreground of the Galactic center, ∼4 kpc. In addition, even the kinematic distances in the literature are inconsistent with each other.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…As a demonstration of the application of mkacispback to actual celestial observations, we applied this tool to the X-ray emission of the supernova remnant G359.1−0.5, which is relatively old among supernova remnants and thus is a faint and diffuse CCD Name source, where the particle-induced background is relatively important (e.g., Suzuki et al 2020). An image of G359.1−0.5 is shown in the left panel of Fig.…”
Section: Application To a Celestial Observationmentioning
confidence: 99%